Respostas
respondido por:
1
-2x+4 >_ x-2
-2x-x >_ -2-4
-3x >_ -6.(-1)
3x <_ 6
x <_ 6/3
x <_ 2
S={x <_ 2}
-2x-x >_ -2-4
-3x >_ -6.(-1)
3x <_ 6
x <_ 6/3
x <_ 2
S={x <_ 2}
nathinha6799:
a resposta certa é menor
respondido por:
1
equação: -2x+4>x-2, resolve-se como igualdade;
-2x+4=x-2
-2x-x=-4-2
-3x=-6, x= -6/-3 = 2 então conjunto x>-2 S= {-2,-1,0,..}
-2x+4=x-2
-2x-x=-4-2
-3x=-6, x= -6/-3 = 2 então conjunto x>-2 S= {-2,-1,0,..}
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás